RESULTS OF THE EFFECT OF POLYOXIDONIUM ON CD25 AND CD95 CONCENTRATIONS IN PATIENTS WITH SEVERE TRAUMA AND THEIR CORRECTION (Academicia Globe: Inderscience Research, 2023)
The purpose of the study: to evaluate the effect of polyoxidonium on the cd25 and cd95 content in the blood serum of patients with severe trauma. Material and methods. The objects of clinical study were 48 patients with polytrauma, the age ranged from 18 to 47 years, men - 34, women — 14. The content of sAPO-1/FAS (cd95+) and the IL-2 receptor (cd25+) were determined by the enzyme immunoassay on the ELIZA apparatus using Bender Medsystems kits. The digital material was processed by the method of variation statistics. Results. The victims with polytrauma showed a sharp decrease in the content of lymphocytes in the peripheral blood in the early stages. There was a significant increase in the level of sCD95 by 1.75 and 1.73 times on the 3rd day, by 1.42 and 1.22 times - on the 7th day after the injury. The analysis of the level showed an increase in sCD25 by 1.6 and 1.29 times on the 3rd day, by 1.35 and 1.22 times - on the 7th and by 1.22 and 1.16 - on the 14th day of the study. The greatest changes were characteristic of patients with combined trauma and the risk of developing post-traumatic infectious and inflammatory processes. In contrast to the values of the control group, the additional inclusion of polyoxidonium led to an earlier restoration of the content of lymphocytes in the peripheral blood of the victims, a decrease in high levels of sCD95 and sCD25. Conclusion: polyoxidonium contributed not only to the restoration of the number of lymphocytes, but also to an increase in their functional activity, especially with the risk of septic complications.